Numerical simulations in a generalized Liénard’s type system - Valdés, Juan E Nápoles; Roa, Paula Macarena (Annals of Mathematics and Physics, 2023)
In this note we present some numerical simulations of the asymptotic behavior of a Generalized Liénard Equation, taking into account a recently defined differential operator. We must point out that these numerical variations have not been obtained as usual: by varying the functions of the right member of the system considered, but, on the contrary, by varying the kernels and the order of the generalized operator used. The above provides breadth and generality to the results obtained, which complement some known in the literature.